2013
DOI: 10.1007/s40070-013-0014-5
|View full text |Cite
|
Sign up to set email alerts
|

Addressing ‘deep’ uncertainty over long-term climate in major infrastructure projects: four innovations of the Thames Estuary 2100 Project

Abstract: Climate change brings new challenges for traditional environmental risk management, particularly for major infrastructure projects, where the decisions made today can have long-term implications. A major challenge is that projections of future climate are deeply uncertain. If this uncertainty is not managed appropriately, long-lived infrastructure may need to be replaced or expensively retrofitted before the end of the design lifetime. The Thames Estuary 2100 Project (TE2100) was one of the first major infrast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
234
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(239 citation statements)
references
References 50 publications
4
234
0
1
Order By: Relevance
“…This includes a reorientation on the impacts of climate change on existing (water) management objectives. This conforms recent studies that have suggested that adaptation research should start from the adaptation problem in its decision context of socio-economic challenges in order to satisfy information needs of policymakers in the face of long-term planning under uncertainty (Kwadijk et al 2010;Ranger et al 2013;Reeder and Ranger 2011). A reorientation would also be useful in cases where adaptation is to be integrated in existing policies.…”
Section: Lessons From the Analysis For The Diagnostic Frameworksupporting
confidence: 88%
See 1 more Smart Citation
“…This includes a reorientation on the impacts of climate change on existing (water) management objectives. This conforms recent studies that have suggested that adaptation research should start from the adaptation problem in its decision context of socio-economic challenges in order to satisfy information needs of policymakers in the face of long-term planning under uncertainty (Kwadijk et al 2010;Ranger et al 2013;Reeder and Ranger 2011). A reorientation would also be useful in cases where adaptation is to be integrated in existing policies.…”
Section: Lessons From the Analysis For The Diagnostic Frameworksupporting
confidence: 88%
“…Many different tools and methods exist to do problem-oriented adaptation research and provide decision support (e.g. Hallegatte et al 2012;Ranger et al 2013;Walker et al 2012;Wise et al 2014). Yet which approach is applicable in which situation?…”
Section: Introductionmentioning
confidence: 99%
“…For instance, risks to coastal infrastructure and low-lying ecosystems can depend strongly on whether sea level rise is moderate or extreme, and to address this, the Australasia assessment separately evaluated risk levels for different sea-level-rise magnitudes. Iterative adjustment of adaptive responses over time can be a way to address such uncertainty about future sea level rise, recognizing that current choices can constrain or expand future options (e.g., Ranger et al 2013). A priority for future assessment and research is rigorous study of adaptation effectiveness, for current and future actions, across the determinants of risk.…”
Section: Features Of the Climate Challenge Emphasized In Key Risksmentioning
confidence: 99%
“…Katsman et al 2011;Ranger et al 2013) is the possibility of an increase beyond the likely range projected by physically based climate models. Such a contribution could originate from additional dynamic ice sheet contributions, linked to the movement of fast ice streams and outlet glaciers.…”
Section: High-end Estimates Of Time-mean Global Sea Level Changementioning
confidence: 99%